Math self-regulated learning assisted by metacognitive support by reviewing sex differences in mathematics anxiety - Fajri, Fenty Rahmawati; Amir, Mohammad Faizal (REID (Research and Evaluation in Education), 2022)
The study aims to analyze the effect of mathematics self-regulated learning (MSRL) assisted by metacognitive support (MS) by reviewing sex differences (SD) in mathematics anxiety (MA). The reason is that MA causes students to have difficulty in learning, so good strategies and approaches are needed. In several studies, there is a relevant relationship between MA, SRL, and MS. This research is quantitative research using Spearman Rho analysis and ordinal regression analysis, with the research population being 3rd-grade students of primary schools in Sidoarjo, East Java. The instruments used in data collection were questionnaires and tests declared valid and reliable. The validity and reliability of the instrument were obtained through content validity assessment and item analysis testing. The results showed a relationship between SRL and MS to MA. There was a positive effect of MS-assisted MSRL in terms of SD on MA. Furthermore, the average student had a positive MS and a high MSRL. The highest MA students are at the moderate level, with a percentage of 79%, and are dominant in the affective aspect. However, when viewed from the SD, the MA showed that female students were more anxious than male students. Thus, the MS-assisted SRL has a good influence when viewed from SD to MA. The recommendation from this research is so that MS and SRL strategies can be implemented optimally. Teachers must prepare and explore the implementation of using the strategies and approach more deeply.